Physiologically acceptable resistance of an air purifying respirator - Shykoff, Barbara E.; Warkander, Dan E. (Ergonomics, 2011)
Physiologically acceptable limits of inspiratory impediment for air purifying respirators (APRs) were sought. Measurements on 30 subjects included pressure in, and flow through, an APR, and respiratory and cardiovascular variables. Exercise with and without APR included ladder climbing, load lift and transfer, incremental running and endurance running, with endurance at 85% peak oxygen uptake. Resistance that did not alter minute ventilation ( ) was judged acceptable long-term. Acceptable short-term impediments were deduced from end exercise conditions. Proposed long-term limits are inspiratory work of breathing per tidal volume (WOB i /V T ) ≤ 0.9 kPa and peak inspiratory pressure (P i peak ) ≤ 1.2 kPa. Proposed short-term limits are: for ≤ 110 L min −1 , WOB i /V T ≤ 1.3 kPa and P i peak ≤ 1.8 kPa; and for > 130 L min −1 , WOB i /V T ≤ 1.6 kPa. A design relation among , pressure-flow coefficients of an APR, and WOB i /V T is proposed. Statement of Relevance: This work generalises results from one APR by considering the altered physiological parameters related to factors inhibiting exercise. Simple expressions are proposed to connect bench-test parameters to the relation between ventilation and work of breathing. Population-based recommendations recognise that those who need more air flow can also generate higher pressures.